The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.21273/hortsci.46.6.870
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plant Bioregulators on Pecan Flowering and Implications for Regulation of Pistillate Flower Initiation

Abstract: Mitigation of alternate bearing (AB) through regulation of floral initiation of pistillate flowers is central to improving cropload management of pecan [Carya illinoinensis (Wangenh.) K. Koch] trees and orchards. The present study examines the influence of key bioregulators {i.e., an auxin [as B-napththaleneacetic acid (NAA)], a cytokinin [6-benylamino purine (6-BA)], an ethylene generator (ethephon), and an auxin transport inhibitor [2,3,5-triiodob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
31
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 44 publications
1
31
0
1
Order By: Relevance
“…Although appropriate fungicide use typically provides satisfactory scab control, protection is expensive, and disease control is often disappointing. In addition, fungicides might reduce carbon photoassimilation Wood et al, 1985), which potentially influences flowering and crop load (Wood, 1989(Wood, , 1995(Wood, , 2011Wood et al, 2003;Worley, 1979aWorley, , 1979b. Thus, there is need for improved scab disease management tools that increase efficacy and/ or reduce control costs without adversely affecting tree health and production potential.…”
mentioning
confidence: 99%
“…Although appropriate fungicide use typically provides satisfactory scab control, protection is expensive, and disease control is often disappointing. In addition, fungicides might reduce carbon photoassimilation Wood et al, 1985), which potentially influences flowering and crop load (Wood, 1989(Wood, , 1995(Wood, , 2011Wood et al, 2003;Worley, 1979aWorley, , 1979b. Thus, there is need for improved scab disease management tools that increase efficacy and/ or reduce control costs without adversely affecting tree health and production potential.…”
mentioning
confidence: 99%
“…), wal-nut (Juglans spp. ), and pecan (Greene, 2000;Hagemann et al, 2015;Hassankhah et al, 2018;Muñoz-Fambuena et al, 2012;Wood, 2011aWood, , 2011bWood et al, 2009). Application of ethephon-suppressed endogenous gibberellin GA 3 (GA 3 ) production in apple when applied in early spring increased subsequent season flowering and fruit set (Ebert and Bangerth, 1981).…”
mentioning
confidence: 99%
“…Exogenous application of ethephon to whole immature trees in Wood's (2011b) study increased both the subsequent season's percentage of new shoots with flowers and the number of nuts per cluster compared with the control group. The ethylene inhibitor AVG was proposed as a mitigation tool for AB because it increases fruit retention in off years and has a carryover effect in which subsequent season on-year production was reduced (Wood, 2011a(Wood, , 2011bWood et al, 2009).…”
mentioning
confidence: 99%
“…Pecan alternate-bearing theories have undergone modification as additional data have become available. Current theory concerning flowering regulation of angiosperm fruit trees (Bangerth, 2009) and specifically pecan (Wood, 2011) states that the level-one signal of the autonomous floral pathway is florigen [a mobile flowering locus T protein (Yang et al, 2007)]. The level-two floral signal appears to involve long-distance signals that engage histones affecting chromatin configuration and thus accessibility to particular genes for transcription (Kouzarides, 2007;Nelissen et al, 2007).…”
mentioning
confidence: 99%
“…The level-two floral signal appears to involve long-distance signals that engage histones affecting chromatin configuration and thus accessibility to particular genes for transcription (Kouzarides, 2007;Nelissen et al, 2007). Phytohormones are candidates for long-distance signals such that gibberellins and auxin inhibit floral induction, whereas cytokinins promote floral induction (Bangerth, 2009;Wood, 2011). In pecan, non-structural carbohydrate concentrations in roots were implicated in pistillate flower differentiation (post-floral induction) (Malstrom, 1974;Smith and Waugh, 1938;Sparks and Brack, 1972;Wood, 1989Wood, , 1991Worley, 1979), but later work demonstrated that abundant stored non-structural carbohydrates were not related to return bloom (Rohla et al, 2007a(Rohla et al, , 2007bSmith et al, 2007).…”
mentioning
confidence: 99%